2012
DOI: 10.1002/ca.22135
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and dissimilarities of the blood supplies of the human sciatic, tibial, and common peroneal nerves

Abstract: The aim was to investigate the arterial supply of the sciatic, tibial, and common peroneal nerves. Thirty-six lower limbs of 18 human fetuses were studied. The fetuses had been fixed in buffered formalin and the blood vessels injected with barium sulfate. Fetal age ranged from 12 to 28 weeks of gestation. Microdissection of the fetal lower extremities was done under ×5 magnifying lenses. The sciatic nerves of 10 lower extremities were dissected and excised and radiographs taken. The extraneural arterial chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
(31 reference statements)
2
19
0
1
Order By: Relevance
“…Anatomists have traditionally considered it to be the persistent sciatic artery 7 ; however, recent studies suggest that most of the accompanying arteries that had been reported were not truly primitive sciatic arteries and should be regarded as representing a secondary anastomosis between the inferior gluteal and popliteal arteries . In fact, the accompanying artery of the sciatic nerve is not a single axial artery but comprises a continuous anastomotic chain of arteries, including the inferior gluteal artery, medial circumflex femoral artery, perforating arteries of the deep femoral artery, and popliteal artery . The findings of our CT angiography study are largely consistent with those of previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Anatomists have traditionally considered it to be the persistent sciatic artery 7 ; however, recent studies suggest that most of the accompanying arteries that had been reported were not truly primitive sciatic arteries and should be regarded as representing a secondary anastomosis between the inferior gluteal and popliteal arteries . In fact, the accompanying artery of the sciatic nerve is not a single axial artery but comprises a continuous anastomotic chain of arteries, including the inferior gluteal artery, medial circumflex femoral artery, perforating arteries of the deep femoral artery, and popliteal artery . The findings of our CT angiography study are largely consistent with those of previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…If the accompanying artery of the sciatic nerve is used as a recipient vessel for free‐flap transfer, ischemia of the sciatic nerve is a concern. As mentioned earlier, the sciatic nerve is not supplied by a single elongated longitudinal artery but is supplied segmentally by numerous arterial branches of different origins . Therefore, we believe that the risk of ischemia of the sciatic nerve would not be present even if the accompanying artery were transected in a single place.…”
Section: Discussionmentioning
confidence: 74%
“…Why nerve segments at the thigh level should be susceptible to microstructural alteration induced by ischemic and/or metabolic mechanisms is unknown. It can be speculated that these nerve segments experience inferior protection by nutritive microvascular supply because they are located at a hemodynamic watershed region of nerve perfusion 33, 34, 35. Altogether, the accumulation of microstructural nerve alterations at the thigh level, which may represent a vulnerable region for ischemic and/or metabolic injury, may precede and possibly trigger distal fiber loss in a length‐dependent manner in which the distal fibers tend to die first.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of vascularization is present in the major trunk of the tibial and sciatic nerves. Two to six arteries are needed to form the extraneural arterial chain of the sciatic nerve, which pass to it from neighboring arteries, perforating, popliteal artery, inferior gluteal, and medial circumflex femoral at the certain level (Ugrenovic et al, 2013).…”
Section: Discussionmentioning
confidence: 99%